MARKETING STUDIES OF ADDITIONAL SERVICES RENDERED IN PHARMACEUTICAL ORGANIZATIONS OF THE REPUBLIC OF NORTH OSSETIA – ALANIA - L. N. Tsarakhova; I. L. Levkova (Фармация и фармакология (Пятигорск))
Market changes in Russian economy have significantly influenced the pharmaceutical market and changed the working conditions of pharmaceutical organizations. Properly formed list of additional services allows enhancing the competitiveness of a pharmaceutical organization. Additional services, which are rendered in a pharmacy organization, can be provided to the population as well as to medical workers and pharmaceutists who work in other organizations. The development of additional services system for pharmaceutical organizations in the Republic of North Ossetia – Alania was the purpose of the study. Content-analysis showed that the significant interest o of pharmaceutical organizations is paid towards the additional service extension. Sociological survey of pharmacy customers, pharmaceutical and medical workers allowed making a conclusion about the fact that list of additional services, rendered by pharmacy organizations is limited and it is necessary to be extended in different directions: pharmaceutical, medical, and therapeutic. Thus basing on the systematization of services, rendered by the pharmacies, and study of demand in additional services we have developed a model of additional services package in pharmaceutical organizations.